Pengembangan Instrumen Penilaian Higher Order Thinking Skills (HOTS) Mata Pelajaran Otomatisasi Tata Kelola Humas dan Keprotokola di SMK Negeri Mojoagung - Achmad Nur Rizal; Siti Sri Wulandari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This study aims to produce a valid and reliable HOTS-based assessment instrument, and describe the quality of the HOTS test questions to measure high-level thinking skills in high school class XI students. problems, data collection, product design, design validation, design revisions, product trials, product revisions, trial usage, product revisions, and mass products. The results showed that the HOTS-based assessment instrument in the form of HOTS test questions consisting of 20 multiple choice questions and 5 item description items from the aspects of material, evaluation, and language were declared valid and feasible to use. Multiple choice questions have an average level of difficulty with moderate criteria, the average differentiation of questions has a very good average, the validity of the items declared valid is as many as 20 multiple choice questions, the reliability coefficient is 0.820 with very high categories, and not all the trickster is functioning properly.